Factor substitution in Swiss manufacturing: Empirical evidence using micro panel data - Sebastian M. Deininger; Lukas Mohler; Daniel Mueller (Swiss Journal of Economics and Statistics, 2018)
This paper analyzes the relationship between factor substitutability and the energy intensity of manufacturing firms. Specifically, we compare the degree of substitutability between the input factors capital, labor, energy, and material for firms with low, medium, and high energy cost shares using a panel of Swiss manufacturing companies covering the period from 1997 to 2008. Our findings indicate substitutability between almost all production factors with one notable exception. Energy and capital are complements in the energy-intensive firm sample: A 1% increase in energy prices decreases capital use by 0.09%. We show that this complementarity is gradually increasing in the energy intensity of firms and draft important policy implications.
Keywords: C33; D24; Q41; 330; Substitution elasticities; Complementarity; Swiss manufacturing; Micro panel data; Linear logit; Translog